Google classroom as a learning management system to teach biochemistry in a medical school. Issue 4 (17th April 2019) - Dash, Sambit
Abstract: Medical education has adopted various e‐learning technologies to its aid. Addition of Google Classroom, introduced in 2014, as a Learning Management System (LMS) has provided a basic, easy to use platform. This study tested its efficacy in teaching a biochemistry module to first year MBBS students in an Indian medical school. Better access to learning material and supplementary teaching resources, helpfulness of immediate feedback, and learning outside of class environment were reported by students. Preference of mobile phone over laptop to access this LMS was reported. Use of this free to use LMS can be made, and especially in resource limited low and middle income countries, to encourage greater access to e‐learning. © 2019 International Union of Biochemistry and Molecular Biology, 47(4):404–407, 2019.